The level of knowledge, use and acceptance of LCA among designers in Germany: A contribution to IEA EBC Annex 72. Issue 4 (November 2020) - Lützkendorf, T; Balouktsi, M
Abstract: Architects and engineers have become more concerned about the environmental consequences of their design solutions. Knowledge about Life Cycle Assessment (LCA) is crucial for the necessary building sector decarbonisation, as well as for mitigating other negative environmental impacts. In Germany, designers' attitudes towards LCA have not been analysed since 2005. However, since then, certain developments – such as the establishment of the sustainability assessment systems BNB and DGNB – have taken place. In 2019, as part of the project IEA EBC Annex 72, a survey was conducted amongst designers in Germany. The paper presents the current status to identify the progress being made since 2005 and provides recommendations to overcome barriers to LCA dissemination. The results show that although German designers are currently doing a lot with regard to environmental performance assessment, the most critical aspects are considered in a more qualitative way, except for the mandatory operational energy performance calculations. LCA-know-how and application still lags behind expectation. To support an increased use of LCA during building design, not only the provision of related data and design/assessment tools is necessary, but also the establishment of standards and regulations. The latter will drive the also necessary client demand.